From Saline to Freshwater: The Diversity of Western Lakes in Space and Time 2021
DOI: 10.1130/2018.2536(08)
|View full text |Cite
|
Sign up to set email alerts
|

Lake Andrei: A Pliocene pluvial lake in Eureka Valley, eastern California

Abstract: We used geologic mapping, tephrochronology, and 40Ar/39Ar dating to describe evidence of a ca. 3.5 Ma pluvial lake in Eureka Valley, eastern California, that we informally name herein Lake Andrei. We identified six different tuffs in the Eureka Valley drainage basin, including two previously undescribed tuffs: the 3.509 ± 0.009 Ma tuff of Hanging Rock Canyon and the 3.506 ± 0.010 Ma tuff of Last Chance (informal names). We focused on four Pliocene stratigraphic sequences. Three sequences are composed of fluvia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Pliocene lake sediments crop out to a limited extent in several valleys east of the Sierra Nevada, California, including Death Valley (Knott et al., 2008), Searles Valley (Rittase et al., 2020), Fish Lake Valley (Reheis et al., 1993), and Eureka Valley (Knott et al., 2019) (Figure 1). From this same region, Pliocene sediment cores are only available from the KM‐3 core of Searles Valley (Liddicoat et al., 1980; Smith et al., 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Pliocene lake sediments crop out to a limited extent in several valleys east of the Sierra Nevada, California, including Death Valley (Knott et al., 2008), Searles Valley (Rittase et al., 2020), Fish Lake Valley (Reheis et al., 1993), and Eureka Valley (Knott et al., 2019) (Figure 1). From this same region, Pliocene sediment cores are only available from the KM‐3 core of Searles Valley (Liddicoat et al., 1980; Smith et al., 1983).…”
Section: Introductionmentioning
confidence: 99%
“…3). Similarly, Knott et al (2019a) showed that the Quaternary lake beds mapped by McKee and Nelson (1967) at location EV (Fig. 2) are also Pliocene sandstone and conglomerate interbedded with the tuff of Zabriskie Wash (3.335 ± 0.002 Ma).…”
Section: Resultsmentioning
confidence: 72%
“…Lower case letters (a, b, c, d, w, x, y, z) are locations from Miller (1928; Fig. 2); location EV in Eureka Valley is from Knott et al (2019). Streams emanating from the White Mountains are Cottonwood Creek (CWC), Crooked Creek (CC), Wyman Creek (WC), and Birch Creek (BC).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations